2003
DOI: 10.1038/nature01440
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of receptor and ligand regulates activation of epithelial growth factor receptor

Abstract: Interactions between ligands and receptors are central to communication between cells and tissues. Human airway epithelia constitutively produce both a ligand, the growth factor heregulin, and its receptors--erbB2, erbB3 and erbB4 (refs 1-3). Although heregulin binding initiates cellular proliferation and differentiation, airway epithelia have a low rate of cell division. This raises the question of how ligand-receptor interactions are controlled in epithelia. Here we show that in differentiated human airway e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
341
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(365 citation statements)
references
References 16 publications
19
341
4
1
Order By: Relevance
“…This segregation provides one answer to the question of how ligand-receptor interactions are controlled in epithelia (Figure 4). In this respect, it was reported that airway epithelia constitutively produced both a ligand, the growth factor heregulin and its receptors, erbB2, erbB3 and erbB4 (Vermeer et al, 2003). However, in cases where TJs were formed, the ligand and receptors were segregated and the receptor activation was silenced.…”
Section: How Segregation Of the Apical And Lateral Microenvironments mentioning
confidence: 99%
See 1 more Smart Citation
“…This segregation provides one answer to the question of how ligand-receptor interactions are controlled in epithelia (Figure 4). In this respect, it was reported that airway epithelia constitutively produced both a ligand, the growth factor heregulin and its receptors, erbB2, erbB3 and erbB4 (Vermeer et al, 2003). However, in cases where TJs were formed, the ligand and receptors were segregated and the receptor activation was silenced.…”
Section: How Segregation Of the Apical And Lateral Microenvironments mentioning
confidence: 99%
“…However, in cases where TJs were formed, the ligand and receptors were segregated and the receptor activation was silenced. This model predicts that increased paracellular permeability as well as complete epithelial disruption would allow the ligand to access its receptors (Vermeer et al, 2003). This system has been recognized as a repair system for damage to epithelial layers (Chao et al, 2003).…”
Section: How Segregation Of the Apical And Lateral Microenvironments mentioning
confidence: 99%
“…366 In intact polarized human airway epithelium, NRG1 and ERBB3 were segregated, the former on the apical membrane, and the latter on the basolateral surface. 367 When the epithelium was disrupted, as in lung injury, NRG1 contacts and activates ERBB3 (and ERBB2). Cell division could then ensue to re-establish epithelial integrity.…”
Section: Respiratory Tissuesmentioning
confidence: 99%
“…A critical feature of polarized epithelia is the different compartmentalization of GFs to the basolateral side and receptors to the apical side, which prevents receptor activation. In one striking case, the loss of polarity of epithelial cells was shown to allow the intermixing of basolaterally localized HER2/ ErbB2, a member of the EGFR family and its activator heregulin, normally secreted to the apical side (Vermeer et al, 2003), leading to cell proliferation (Figure 4). Although this mechanism is responsible for wound healing of the respiratory epithelium in response to various types of aggression, it is not difficult to imagine the involvement of similar mechanisms in neoplastic transformation of epithelial cells.…”
Section: How Cancer Hijacks the Epp Machineriesmentioning
confidence: 99%